Stratabound Zinc-Lead mineralization in the Phakuwa area Sankhuwasabha district, eastern Nepal - Tuladhar, R. M. (Journal of Nepal Geological Society, 1991)
A massive to disseminated stratabound zinc-lead mineralized horizon confined within the metamorphosed sequence (Phakuwa Group) of the Kathmandu Complex has been traced for over a strike length of one kilometer in the Phakuwa area of the Sankhuwasabha District in eastern Nepal. Its geotectonic setting, metamorphism and deformation and above all, style of mineralization are comparable with the Ganesh Himal zinc-lead deposit Detailed ore-mineralogical studies from both areas revealed similar mineralogical assemblages and associations. Electron microprobe analyses of common sulphides resulted in analogous mineral chemistry which is strongly indicative of similar depositional environment of these two deposits.